The Efforts of the Traffic Education Unit in Reducing Traffic Accidents in the Legal Area of the Semarang Police Station - Rizky Alief Dharmawan (Advances in Police Science Research Journal, 2022)
This research was motivated by the high number of traffic accidents that occurred in the jurisdiction of the Semarang Polrestabes in the last three years. Based on Law no. 2 of 2002 concerning the duties of the police, Law no. 22 of 2009 concerning road traffic and transportation, and Juklak/5/V/2003 concerning public education in the field of traffic, so that through preemptive steps In responding to this problem, the Semarang Polrestabes Satlantas has made efforts through the traffic education unit with the aim of reducing traffic accidents that cause traffic accidents. exist and increase public awareness of the importance of past kamseltibcar. However, there are several obstacles and obstacles in the implementation of direct education in the field. Some of the factors that influence the implementation of the social education program in reducing traffic accidents and creating security and safety regulations are discussed using the concept of effort, the concept of direct social education, and the theory of 6M management elements put forward by George R. Terry which consists of six elements, namely man, money, methods, materials, machines, and markets. Based on the results of the research conducted, the authors suggest that there is a need for a change in the focus of providing education and social services directly, changing the method of providing social media services using social media, reviewing the fulfillment of the number of personnel, providing vocational education for personnel, better budget management, as well as maintenance and procurement of infrastructure that has not yet been completed. available. In order to maximize the efforts of the direct social and community education unit in reducing traffic accidents and increase public awareness of the importance of traffic security and safety in the future.